THE INFLUENCE OF SELF-REWARD AND SELF-EFFICACY ON ACCOUNTING STUDENTS' LEARNING MOTIVATION WITH SELF-REGULATED LEARNING AS A INTERVENING VARIABLE: Array - Restu - Gustiawan; Sukma Nazah Al Azhar (STIESA Press, 2025)
This study examines the effect of Self-Reward and Self-Efficacy on accounting students' learning motivation, with Self-Regulated Learning (SRL) as a mediating variable. Learning motivation is a crucial factor in academic success, especially in a competitive and complex higher education environment such as accounting, which demands conceptual understanding and technical skills. This study was motivated by the inconsistency of previous research findings regarding the mediating role of SRL and the neglect of self-reward variables in learning motivation models. Using a quantitative approach and a sample of 51 accounting students from various universities, this study seeks to provide empirical clarity regarding SRL mechanisms specific to the accounting context, as well as integrating self-reward as a key variable. The results showed that Self-Efficacy and Self-Regulated Learning have a positive and significant influence on the learning motivation of accounting students. Students with high self-efficacy tend to be more motivated and able to regulate their learning process independently, which in turn increases learning motivation. Although self-reward was found to have a significant effect on Self-Regulated Learning, its effect on learning motivation directly was not significant in this study. However, Self-Regulated Learning was shown to mediate the effect of Self-Efficacy on learning motivation. These findings underscore the importance of developing self-efficacy and effective SRL strategies in the accounting curriculum to enhance students' motivation and academic achievement.